Without any doubt Gersonides on method and knowledge - Klein-Braslavy, Sara. (Supplements to The Journal of Jewish Thought and Philosophy, 2011)
Gersonides-Rabbi Levi ben Gershom (Provence, 1288-1344)-was a multifaceted thinker. Endowed with his original and critical mind, he did not accept the authority of his predecessors but investigated every matter for himself. His extraordinary attention to method-both of inquiry and of writing-stands out clearly in his own work and in his reading of certain biblical books. The eight articles on Gersonides' thought and method collected in this volume address four main topics: Gersonides' methods of inquiry and composition; the use of introductions in his own works and in biblical books; his method in the supercommentaries on Averroes; and his methods of biblical exegesis. \'Klein-Braslavi's (sic) book...is highly recommended for all libraries that take seriously philosophy, the life of the mind and cognition.\' David B. Levy, Touro College